PERKAWINAN TUNGKU CU (CROSS-COUSIN MARRIAGE) DI MANGGARAI: ANTARA ADAT DAN AGAMA - Yohanes S Lon (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:The Manggarai people in Flores have various types of marriage. One of them is “tungku cu” (cross-cousin) marriage. In this model of marriage, a daughter of a brother can marry a son of the sister. So the couple is the two biological cousins. This local tradition considered this marriage as an ideal type. It is believed to strengthen the kinship and to keep the family inheritance, properties and assets from transferring to other clans. But by the coming of religions to this region, especially Catholicism that has become the major religion entire the area, this marriage is called into question. The Catholic Church law strictly forbids this marriage for health reason and for its closeness on the social relations. The Catholic Church will not legalize such kind of marriage. The couples have to ask for dispensation to get the legality of marriage. The process may long and difficult to get the dispensation. This is a controversy. This article aims to explore the tungku cu (cross cousin) marriage in Manggarai. Using a field and literature approach, this study found that despite the controversy, many families still support the model of marriage. This lead them to difficulties in having legal rights of marriage both according to the Church and the state. However, after years, the Church will offer them dispensation by which the couple could have legal status of their marriage. Dispensation has functioned as a negortiation between local culture and religion.Keywords: Cross-cousin, Local Tradition, Marriage, Dispensation, Catholic Church, Manggarai Abstrak:Orang Manggarai mengenai aneka jenis perkawinan. Salah satunya adalah perkawinan tungku cu atau cross-cousin marriage. Dalam model perkawinan ini, anak perempuan dari saudara laki-laki dapat menikah dengan anak laki-laki dari saudari. Jadi yang menikah adalah dua sepupu kandung. Perkawinan ini dalam tradisi lokal dianggap ideal. Perkawinan ini memperkuat hubungan kekerabatan serta dipercaya dapat menjaga supaya harta tidak berpindah ke clan lain. Namun dengan datangnya agama-agama di wilayah ini,, khususnya agama Katolik sebagai agama mayoritas, perkawinan ini dipertanyakan. Hukum Gereja dengan tegas melarang perkawinan ini dengan alasan biologis yaitu dapat membayakan kesehatan bagi keturunan yang dilahirkan dan mempersempit relasi sosial. Olehnya Gereja tidak memberikan legalitas bagi pasangan tungku cu, kecuali dengan sebuah dispensasi yang tidak mudah didapatkan. Hal ini menjadi kontroversi. Artikel ini bertujuan untuk mendalami perkawinan tungku cu pada masyarakat Manggarai ditinjau dari perspektif hukum perkawinan Gereja Katolik. Dengan menggunakan pendekatan kepustakaan dan studi lapangan. Studi ini menemukan bahwa kendatipun kontroversial, masih banyak keluarga masih mendukung perkawinan model ini. Maka dispensasi mau tidak mau menjadi negosiasi dan jalan keluar untuk menyatukan agama dan adat lokal.Kata Kunci: Cross-cousin, adat, perkawinan, dispensasi, hukum Gereja Katolik, Manggarai